Effect of gravel content on the sediment transport capacity of overland flow - Zhan, Zhenzhi; Jiang, Fangshi; Chen, Peisong; Gao, Pengyu; Lin, Jinshi; Ge, Hongli; Wang, Ming Kuang; Huang, Yanhe (Catena (Giessen), 2020)
•Gravel content affected transport capacity (Tc) on non-erodible rills was studied.•Measured Tc increased linearly as gravel content increased.•New equations were established to predict Tc on colluvial deposits with gravel content. The sediment transport capacity (Tc) is an important parameter for analysing and controlling soil erosion processes. However, few studies have investigated the Tc of soils containing gravel (grain sizes of >2 mm) on steep slopes. Colluvial deposits on steep slopes in benggang are composed of loose materials with large amounts of gravel. This study aimed to investigate the effects of gravel content on the Tc of overland flow using colluvial deposits with a range of slope gradients and flow discharges in a nonerodible flume (4 m long, 0.12 m wide and 0.1 m high). The experiments were carried out using six gravel mass contents (0, 10, 20, 30, 40, and 50%), four slope gradients (18, 36, 57, and 84%), and four flow discharges (0. 56, 1.11, 2.22, and 4.44 × 10-3 m2 s−1). The experimental results revealed that the measured Tc increased linearly as the gravel content increased. The effects of the slope gradient, flow discharge and gravel content on Tc were significant (p < 0.01). Tc increased following power functions either with slope gradient, flow discharge and gravel content (coefficient of model determination (r2) = 0.96 and Nash-Sutcliffe model efficiency (NSE) = 0.96), or with slope gradient, flow discharge and sediment median grain size (d50) (r2 = 0.98 and NSE = 0.98). The two established power functions facilitated the prediction of the Tc of colluvial deposits in this study. However, the power functions overestimated the predicted Tc values when the measured Tc was less than 1 kg m−1 s−1 and underestimated the values when the measured Tc ranged from 2 to 4 kg m−1 s−1. These findings are helpful for improving the simulation of erosion processes in colluvial deposits and deepening the understanding of erosion mechanisms in soil and rock mixtures. Moreover, the relationship of hydrodynamic variables with Tc on colluvial deposits remains to be investigated in additional in-depth studies.